Petrology, Geochemical Characteristics, Tectonic Setting, and Implications for Chromite and PGE Mineralization of the Hongshishan Alaskan-Type Complex in the Beishan Orogenic Collage, North West China - Wang, Zhaolin; Zheng, Xiaoming; Meng, Guixiang; Tang, Hejun; Fang, Tonghui (Frontiers in Earth Science, 2021)
Abstract: The Hongshishan mafic–ultramafic complex is situated in the north of the Beishan orogenic collage, the southern part of the Central Asian Orogenic Belt. This paper details petrology, geochemical, mineralogical data of an ultramafic–mafic intrusion in the Hongshishan complex from Beishan orogenic collage to infer possible tectonic setting for the magma. The main lithological units of the complex include dunite, clinopyxene peridotite, pyroxenite and gabrro. The complex shows a concentric zonation, from clinopyxene peridotite and dunite in the core, to mafic intrusions including pyroxenite and gabrro in the margin. These lithologies typically feature cumulate textures and layering. Field observations, petrography and major element composition variation, the crystallization sequence from dunites, through clinopyxene peridotite and pyroxenite, to gabbros shows a system decreasing sequence of ferromagnesian minerals (Mg#), olivine Fo and spinel Cr#, which show fractional crystallization trends. Olivines from the dunite and clinopyxene peridotite in Hongshishan plot within in the Alaskan Global trend fields and display a typical fractional crystallization trend similar to olivines in Alaskan-type complexes. The clinopyroxenes in the clinopyxene peridotite are mostly classified as diopside and plot in the field of Alaskan-type complex. There are systematic trends among the major element oxides, e.g. CaO, TiO2 and Al2O3, with MgO, suggesting a fractional crystallization trend. The increase in SiO2 and Al2O3 with decreasing MgO suggesting olivine fractionation. The negative correlations of CaO and Al2O3 with MgO mean accumulation of spinel and mafic minerals. Absence of orthopyroxene and nearly all minerals contain less hydrous or free of fluid inclusions mean that subduction-related fluid, melt are not necessarily account for the LILE-enrichment and HFSE-depletion of peridotite rocks in this complex. Negative Eu anomalies and REE fractionation of mafic-ultramafic rocks may not directly attribute to crustal assimilation. Petrological, mineralogical and geochemical characteristics indicate that Hongshishan complex is not the member compositions of typical ophiolite yet displays many similarities with typical Alaskan-type mafic-mltramafic intrusions but formed in intracontinental rift rather than subduction-related setting.